"PROYECTO DE FACTIBILIDAD PARA IMPLEMENTACIÓN DE UNA EMPRESA PRODUCTORA DE ACEITE DE CANNABIS (CBD) PARA USO MEDICINAL EN LA CIUDAD DE LOJA" - SILVA VIVANCO, SANDRO STALIN (2024)
The study examines the feasibility of establishing a company to produce cannabis (CBD) oil for medicinal use in the city of Loja, Ecuador. The market, technical-administrative design, and financial evaluation of the project were the three main elements analyzed. The market study found that CBD products are experiencing growing demand due to the trend toward natural alternatives to medical treatments. This represents an attractive business opportunity. The technical design included planning the necessary infrastructure and efficiently organizing human and material resources to ensure an efficient production process. A clear administrative structure was created to allow proper operational control and efficient resource management. In the financial analysis, indicators such as the Internal Rate of Return (IRR) and Net Present Value (NPV) were used, which confirmed the project's profitability, with an IRR of 49%, significantly higher than the investment rate of 9.76%. In the short term, the project will reach its break-even point, ensuring long-term sustainability and favorable returns for investors. The study concludes that the project is technically and financially viable, and its implementation is recommended. Furthermore, to ensure the project's success, it is advised to conduct regular market studies, provide continuous staff training, and maintain rigorous cost management. The Loja region will benefit economically and socially from this business opportunity.